Plantae colombianae, ix: nova species senefelderae.--de natura ecologica montium arenariosaxosorum insulatorum vaupesense regionis brevis conspectus. (1944)
In March, 1943, Mr. Jules de Wael Mayer, Special Representative of the Rubber Development Corporation in Bogotá, sent me (1) into the upper Apaporis River Basin to initiate explorations of this part of eastern Colombia. The chief purpose of the explorations was a study of Hevea and other commercially valuable lactiferous plants and possibilities of their exploitation. In connection with this work, it was possible to make a cursory examination of the vegetation in general and limited collections of the more interesting species.